Machinability improvement of gear hobbing via process simulation and tool wear predictions. Issue 9 (October 2016) - Dong, X.; Liao, C.; Shin, Y.C.; Zhang, H.H.
Abstract Typical processes of producing transmission gears involve hobbing, milling, or shaping of a forged stock to obtain the desired gear geometries. Among all these machining processes, gear hobbing is an efficient method of manufacturing high-quality gears. In this paper, a three-dimensional (3D) finite element model is presented to simulate the gear hobbing processes. The model is used to simulate the complicated kinematic motion between the hobbing tools and the gear workpieces and to perform a coupled thermo-mechanical analysis on the tools and the workpieces during the chip removal process. Cutting forces, torques, and temperature and stress distributions of the hobbing tools and workpieces are predicted using the proposed model. The tool wear progression in gear hobbing is analyzed in terms of tool geometry by a combined experimental-analytical method. The model considers the complex geometry of hob tooth profiles with multiple teeth engagement and can provide more insights into complicated gear hobbing processes. Based on the simulations with various tool geometries, a new tool geometry is arrived, which reduces spindle torque and shows a significant tool wear reduction. The modeling results are further validated through a direct comparison between the predicted and measured chip shape, torque, and tool wear rate.